Role Play-Based English Module to Improve Speaking Skills of Grade X Students - Rani Elisabeth Sormin; Putri Dyah Ayu Pamuji; Anggraini Thesisia Saragih; Khairul Azmi Siagian (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study aims to develop an English learning module based on the role play approach to improve the speaking skills of Grade X students at SMA Negeri 21 Medan. The study is motivated by students’ low speaking ability due to limited communication practice and the use of conventional teaching methods. This research employs a qualitative approach focusing on needs analysis and initial product development. The research subjects include English teachers and Grade X students who participated in the needs analysis questionnaire. The findings indicate that students require interactive, communicative, and contextual learning and show strong interest in role play activities. Based on these findings, a role play-based module was designed to support speaking practice. However, this study is limited to the design and development stage and has not yet conducted expert validation or field testing. Therefore, further research is recommended to evaluate the feasibility, practicality, and effectiveness of the developed module.